Rolling-free self-compacting ardealite base road construction method
By using a combination of phosphogypsum, cement, slag and aggregate in the road base layer, combined with the roll-free construction process, the problem of insufficient clumping and hydration reaction of phosphogypsum powder in the road base layer is solved, and the water is improved Stability and durability achieve the effective utilization of phosphogypsum solid waste and the efficient construction of road base.
Patent Information
- Application Number
- CN202411092442.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing phosphogypsum powder in the road base layer has problems such as clustering, uneven mixing, uneven rolling, insufficient hydration reaction, and poor water stability and durability in the later stage.
Phosphogypsum, cement, slag, aggregate and admixture are used as base materials, and uniform and dense mixture is formed through centrifugal mixing. The construction is carried out using a roll-free pouring process. The material usage and water-cement ratio are strictly controlled, and mandatory use The mixer is used to mix, and optimize the mass ratio of phosphogypsum and gelling material to control the formation of ettringite to alleviate the self-shrinkage of the material and prevent road cracking.
It improves the water stability and durability of the road base layer, reduces the amount of cement, realizes the recycling of phosphogypsum solid waste, ensures the early and later strength of the road base layer, prevents cracking, and improves the density and compressive strength.
Smart Images

Figure CN119121723A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of road construction, and in particular to a method for constructing a road with a self-compacting phosphogypsum base without rolling. Background Art
[0002] Phosphogypsum is a solid waste produced when phosphate rock powder is used to produce phosphoric acid and ammonium phosphate fertilizers in the industry. Every ton of phosphoric acid produced produces about 4.5 to 5 tons of phosphogypsum. my country produces a large amount of phosphogypsum every year. Since phosphogypsum contains various impurities such as free carbon, hydrochloric acid, and sulfuric acid, it is difficult to fully utilize. At present, the main treatment method for phosphogypsum is accumulation, which not only occupies a large amount of land, but also contains harmful heavy metal chemicals such as arsenic, cadmium, and mercury, which will pollute the environment.
[0003] With the rapid development of the domestic transportation industry and the increase in the total mileage of road construction, the demand for road base materials in highway construction is huge. Phosphogypsum has a certain hydration hardening strength. If it is used in road construction, it can not only consume a large amount of phosphogypsum, but also greatly reduce the construction cost of the road, which has significant social and economic benefits.
[0004] At present, there are two main directions for the application of phosphogypsum in road base, namely phosphogypsum aggregate system and phosphogypsum powder system. The phosphogypsum aggregate system is a system in which the phosphogypsum raw material is modified and then mixed with phosphogypsum, cementitious materials and auxiliary materials through processes such as centrifugal rolling and pressure molding to form phosphogypsum-based high-strength lightweight aggregates of different particle sizes to replace a small part of the crushed stone in the traditional water-stabilizing layer, prepare a phosphogypsum lightweight aggregate stabilization layer, and use it for the road base by paving and rolling. The advantage of this technology is that through layer-by-layer wrapping, the phosphogypsum consolidation and passivation effect is good and the performance is stable. The disadvantages are that the aggregate preparation process is complicated, the cost is high, the phosphogypsum consumption is low, and it is difficult to achieve large-scale utilization and large-scale market promotion. The phosphogypsum powder system is a large amount of phosphogypsum as a powdery filler, which is mixed with coarse and fine aggregates, cementitious materials and modified curing agents to form a mixture, and applied to the road water-stabilizing layer through traditional paving and rolling construction methods. The advantages of this technology are: simple construction process, phosphogypsum dosage can reach more than 45% (a medium-high dosage), and the cost is controllable. The disadvantages are that the moisture content of phosphogypsum is difficult to control, the powder is easy to clump, the mixing is uneven, the rolling density is insufficient, the hydration reaction is insufficient, and the later water stability and durability are poor. Summary of the invention
[0005] The main purpose of the present invention is to provide a rolling-free self-compacting phosphogypsum base road construction method to solve the technical problems such as the phosphogypsum powder is easy to agglomerate, uneven mixing, loose rolling, insufficient hydration reaction, and poor later water stability and durability. In addition, the construction process of the present invention is simple and can be widely used in base road construction of various grades.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is: A rolling-free self-compacting phosphogypsum base road construction method comprises the following steps: S1 Construction preparation: Clean the construction site, use a sweeper to remove obstacles and debris from the pavement on the construction site, mark the contour and slope of the road according to the road design depth requirements, and then level and compact the road surface. The compaction degree should not be less than 96%, and the deflection of the roadbed top surface should not be greater than 248 (0.01mm). Sprinkle water to moisten the road surface before paving; S2 Base material preparation: phosphogypsum, cement, slag, aggregate and admixture, and water are used as raw materials for the phosphogypsum road base mixture, and various raw materials are centrifugally mixed according to a determined mass ratio to obtain a uniform and dense phosphogypsum base mixture; S3 base paving: transport the evenly mixed mixture to the construction site for paving. After paving, maintain it to form the road base.
[0007] The phosphogypsum road base material prepared by mixing phosphogypsum, cement, slag, aggregate, admixture and water as raw materials can effectively ensure the strength of the road base, improve the water stability and durability of the road, and compared with conventional cement-stabilized crushed stone and C10 low-grade plain concrete, not only the amount of cement is greatly reduced, but also the recycling of phosphogypsum solid waste is realized, with significant economic benefits.
[0008] Furthermore, step S1 also includes installing the construction formwork: the formwork system adopts a wooden formwork or a steel formwork, and the formwork should have sufficient strength, rigidity and overall stability. Before construction, the surveying personnel lay out the formwork installation edge line and use a steel bar to drive it into the ground for fixation to ensure that the formwork is firmly installed without loosening, running, or sinking. The joints are tight and there is no leakage of mortar. The inside of the formwork is kept clean, and a line is drawn on the top of the formwork to mark the control line of the top surface of the base layer.
[0009] Furthermore, in step S2, the particle size of the phosphogypsum used is 5-45 μm, the attached water (wet basis) is not more than 12%, and the content of calcium sulfate dihydrate (dry basis) is not less than 90%.
[0010] Further, in step S2, the cement strength grade is ordinary Portland cement of 42.5, the fineness is expressed by the residue on a 45 μm square sieve, not less than 5%; the initial setting time is not less than 45 min, and the final setting time is not more than 600 min; the stability is qualified by the boiling method, and the chemical requirements (mass fraction) are that the loss on ignition is not more than 5%, SO3 is not more than 3.5%, MgO is not more than 5%, and chloride ion is not more than 0.06%; the main chemical components are CaO (64-67%), SiO2 (20-23%), Al2O3 (4-8%), and Fe2O3 (3-6%); The slag is S95 grade granulated blast furnace slag powder with a density of not less than 2.8g / cm 3 , specific surface area not less than 400m 2 / kg, 28-day activity index not less than 95%, fluidity ratio not less than 95%, initial setting time ratio not more than 200%, water content not more than 1%, SO3 (mass fraction) not more than 4%, loss on ignition not more than 1%, insoluble matter (mass fraction) not more than 3%; the main chemical components are CaO (34-36%), SiO2 (34-36%), Al2O3 (16-18%), and Fe2O3 (1~2%).
[0011] Furthermore, in step S2, the aggregate used is a mixture of crushed stone and sand, wherein the crushed stone adopts continuously graded crushed stone, which is fine crushed stone with a particle size of 5-10 mm and coarse crushed stone with a particle size of 10-20 mm, with a mass ratio of 3:7; the sand adopts machine-made fine sand with a particle size less than 4.75 mm; and the sand-to-stone ratio is 0.2-0.3 to ensure good fluidity of the mixture.
[0012] Furthermore, in step S2, the base material includes phosphogypsum, crushed stone, sand, cement, slag and admixtures, with a mass ratio of 40~50:30~41:8~10:1~4:3~9:0.2~0.7; and a water-cement ratio of 4.5-7.5.
[0013] The present invention strictly controls the dosage of phosphogypsum, cement and mineral powder (mass ratio is 40-50:1-4:3-9), thereby ensuring the water stability and compressive strength of the obtained road base, effectively coordinating the early strength and late strength of the road base, reducing the influence of impurities in the phosphogypsum on product performance, and improving the water stability of the road base to prevent cracking.
[0014] Furthermore, the mass ratio of the phosphogypsum to the cementitious material is 4-6:1, which controls the formation of calcium aluminate, alleviates the self-shrinkage of the material, and prevents road cracking.
[0015] Furthermore, in step S2, the mixing is firstly to uniformly mix part of the phosphogypsum and an appropriate amount of water to form a first mixture; to mix the cementitious material, the remaining phosphogypsum, aggregate, admixture and the remaining water to form a second mixture; and to mix the first mixture and the second mixture to form a third mixture.
[0016] Furthermore, the water and admixture are metered in a coarse and fine metering manner, with two-stage batching, a large initial flow rate to ensure efficiency, a small final flow rate to ensure accuracy, valve-controlled cut-off, and rapid flow interruption; 250-350 kg of water is used per cubic meter of mixture.
[0017] Furthermore, the mixing is carried out using a forced mixer. This mixing method not only makes the cement slag evenly dispersed in the crushed stone and machine-made sand, which is not easy to clump, but can effectively improve the concentrated cracks in the road surface caused by the unevenness of some cement slag; it also gives full play to the alkali-activated characteristics of cement, and part of the phosphogypsum participates in the hydration, thereby making the hydration of the slag more complete. The three are fully mixed and combined to generate a higher strength hydrated cementitious material, thereby enhancing the strength of the mixture.
[0018] The invention uses phosphogypsum, cement, slag and sand and gravel as basic raw materials, wherein calcium hydroxide formed by cement hydration reacts with free alumina and silicon oxide in slag to obtain calcium silicate and calcium aluminate, and these gelled products are further hydrated to form calcium silicate and hydrated calcium aluminate to enhance strength; sand and gravel are designed according to grading theory, and different aggregate particle sizes are matched to form a tightly arranged multi-level space skeleton structure system with maximum friction; due to the excess of CaSO4·2H2O in phosphogypsum, the hydrated calcium silicate gel formed by hydration wraps the aggregate particles in the multi-level space skeleton structure, and Calcium aluminate hydrate reacts with calcium sulfate in phosphogypsum to obtain calcium vanadate, so that long rod-shaped calcium vanadate crystals are interspersed and overlap each other to form a stable structure. The crystallization and coarsening of the calcium silicate hydrate gel in the later stage further increase the stability of the structure. At the same time, the micro-expansion of the calcium vanadate crystals can further compact the structure. The mesh and flocculent calcium silicate hydrate gel that is still being generated in the later stage has good elastic-plastic properties and microporous structure, which can greatly buffer the pressure damage that may be caused by excessive expansion of the calcium vanadate crystals, thereby improving the density and strength of the base material mixture.
[0019] Preferably, the admixtures include a slow-release agent and a water reducer, accounting for 0.3-0.4% of the total mass of the mixture.
[0020] The water reducer is a polycarboxylate water reducer, and the retarder is citric acid; the mass ratio is 1:0.1-0.3; the slow-release agent can stimulate the activity of slag powder and promote the formation of hydration products on the one hand, and control the hydration speed and prolong the setting time of cement on the other hand. An appropriate amount of citric acid can make the pores of the material smaller and more evenly distributed, which is beneficial to improving the density and durability of the base material; Preferably, the admixture also includes an anti-cracking agent, which is polypropylene fiber; accounting for 0.01-0.03% of the mass of the admixture; the polypropylene fiber can effectively control the shrinkage of the material and microcracks caused by temperature changes, prevent the occurrence and development of cracks, and greatly improve the material's crack resistance, impermeability and impact resistance. Since polypropylene fiber has good ductility, after adding polypropylene fiber, the bridging effect of polypropylene fiber inhibits the expansion and formation speed of cracks, thereby improving the performance of the material and achieving the effect of preventing cracking.
[0021] Furthermore, in step S3, the mixture is paved by a paving process. Before pouring, the lower bearing layer is roughened, and the inner side of the formwork is sprinkled with water to moisten it. During paving, a mixer truck is used for self-unloading paving. A horizontal polyurethane expansion joint plate perpendicular to the center line of the road is left every 30 meters. The width of the expansion joint plate is 20mm. In addition, manual assistance is used to control the elevation of the top surface of the base and the horizontal and vertical slopes. After paving, the surface is leveled and roughened to increase the roughness. At the same time, the slump expansion degree is ensured to be 550mm±50 during paving, and the expansion time T 500 ≥2s, thereby effectively ensuring the self-compactness and compressive strength of the road base.
[0022] Furthermore, step S3 also includes maintenance, seam cutting and seam filling: after the base layer is paved, the surface is sprayed with a polymer curing agent twice for maintenance. The first spray is applied during initial setting, and the second spray is applied in a vertical direction after the curing agent has basically formed a film. The curing time is not less than 7 days, and vehicles are prohibited from passing during the curing period. After final setting, seam cutting and seam filling are carried out in a timely manner. A transverse contraction joint is cut perpendicular to the center line of the road every 10 meters using road cutting equipment. The seam width is 5 to 8 mm and the depth is not less than 1 / 3 of the thickness of the single-layer base layer. After cutting, the debris in the seam is cleaned and the seam is filled with asphalt jelly. The reserved transverse polyurethane expansion joint plate has its top expansion joint cleaned to a depth of 2 to 3 cm, and then the seam is filled with asphalt jelly.
[0023] The present invention controls the amount of each component of the road base material and adopts a rolling-free casting process for construction, thereby effectively ensuring the density and structural strength of the water-stabilizing layer.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The road base material of the present invention uses slag powder as the main active cementitious material, cement as an alkali activator, and a small amount of phosphogypsum to participate in the hydration reaction to form a composite modified cementitious material. By optimizing the mix ratio design, the composite modified cementitious material, phosphogypsum, aggregate, admixture and an appropriate amount of water are forced to be centrifugally mixed to form a fluid, fully hydrated, uniform and dense phosphogypsum base material for road base construction.
[0025] 2. The present invention modifies the cementitious material and strictly controls the mass ratio of phosphogypsum, cement and slag powder, which can not only fully exert the activity of the slag powder but also effectively offset the influence of impurities in the phosphogypsum on the strength of the obtained road base structure, thereby ensuring the early and late strength of the base structure; and by using a smaller amount of cement and composite admixtures, the product can be effectively prevented from cracking.
[0026] 3. In the mixing of the mixture, the present invention adopts a forced stirring process instead of a continuous mixing process of water-stabilized materials to ensure uniformity of the mixture and sufficient generation of hydration products; and adopts a paving self-compacting process instead of a traditional rolling process to improve the compactness and impermeability of the road base.
[0027] 4. The construction method of the present invention has the characteristics of reliable performance, simple process and good economy, meets the roadbed strength requirements, can be widely used in various grades of road bases, and plays a role in quickly consuming phosphogypsum and reducing inventory stacking pressure, thereby achieving the effect of resource utilization and turning waste into treasure. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1 This is the XRD diagram of the self-compacting phosphogypsum base material sample of the test example of the present invention. DETAILED DESCRIPTION
[0029] The invention provides a rolling-free self-compacting phosphogypsum-based road construction method, which uses a self-compacting phosphogypsum-based material to be paved by a casting process, wherein the self-compacting phosphogypsum-based material comprises phosphogypsum, cement, slag powder, sand and gravel, and an admixture. The invention optimizes the mix ratio of the phosphogypsum-based material, forces the cementitious material, phosphogypsum, aggregate, admixture, and an appropriate amount of water to be centrifugally mixed, and forms a phosphogypsum-based material that is in a fluidized state, can be fully hydrated, and is uniformly dense.
[0030] The mass ratio of phosphogypsum and cementitious materials in the present invention is crucial, which seriously affects the strength and stability of the base material. Cement mainly provides a sufficient alkaline environment for the system to stimulate the activity of slag powder, but too high cement content will lead to the formation of too much calcium hydroxide, destroy the cementitious materials, and affect the structural strength of the product, while the amount of slag powder added affects the amount of hydration products generated. With the increase of slag powder content, more and more hydration cementation products are produced, which is beneficial to improve the bonding strength of the product. However, when the ratio of mineral powder to cement is too high, the activity of the active component cannot be fully stimulated. Therefore, when controlling the cement content, the mass ratio of mineral powder to cement should be controlled to 2~3.5:1, so that the activity stimulation of slag powder and the degree of hydration reaction can be optimally matched. In addition, with the increase of slag powder content, the shape of ettringite changes from coarse rods to thin rods; when the mass ratio of slag powder to cement is 2~3.5:1, finer needle-shaped ettringite structure appears in the product, and more thin-flaked CSH gel is formed. A large amount of needle-shaped ettringite and thin-flaked gel fills the gaps between particles, forming a denser structure inside the sample, which is reflected in the improvement of the compressive strength of the sample on a macroscopic level.
[0031] In summary, the present invention, by modifying the cementitious material and strictly controlling the mass ratio of phosphogypsum, cement and slag powder, can not only fully exert the activity of the slag powder but also effectively offset the influence of impurities in the phosphogypsum on the strength of the obtained road base structure, thereby ensuring the early and late strength of the base structure and preventing the product from cracking; at the same time, the present invention adopts a rolling-free paving process, which effectively improves the density and anti-seepage and anti-compression properties of the base road.
[0032] In the present invention, since phosphogypsum as fine aggregate accounts for a large proportion, in order to make the self-compacting phosphogypsum base material have good fluidity, small-size crushed stone is used, and the content of needle-like crushed stone is strictly controlled, so that the sand-stone ratio is controlled at 0.2-0.3. Aggregates are designed according to the grading theory, and different aggregate particle sizes are matched and filled in the base material to form a tightly arranged multi-level spatial skeleton structure system with maximum friction, thereby improving the mechanical properties of the material.
[0033] The present invention first optimizes the proportion of each component of the phosphogypsum road base material through a large number of experiments, and then obtains the optimal proportion of each component to prepare the phosphogypsum road base material, and then adopts the construction method of the present invention to further apply it to base road paving, and performs performance evaluation; the construction method of the present invention is simple and reliable, has significant economic, social and environmental benefits, and is suitable for application and promotion.
[0034] Refer to the "Ordinary Concrete Mix Design Code" (JGJ55-2011), and the preparation strength is determined by referring to the following formula: f cu,0 ≥ f cu,k +1.645σ; f cu,0 ---Preparation strength (MPa); f cu,k --- Design strength (MPa); σ---Strength standard deviation (MPa). According to GB / T50107-2010 "Concrete Inspection and Evaluation Standard", the calculated laboratory test block strength standard deviation σ=3.13MPa.
[0035] The design indicators of the original pavement base are that the unconfined compressive strength of the upper and lower bases is not less than 4.0MPa, and the unconfined compressive strength of the bottom base is not less than 3.0Mpa; the prepared strength is: the upper and middle bases are not less than 9.15MPa, and the lower base is not less than 8.15Pa.
[0036] Embodiment 1: A method for preparing a self-compacting phosphogypsum road base material comprises the following steps: Weigh the following base materials by mass percentage: phosphogypsum 45%, crushed stone 35.1%, machine-made sand 8.2%, cement 2%, slag powder 9.0%, admixture 0.7%; 85% of the total amount of phosphogypsum and 65% of the total amount of water are placed in a forced mixer and stirred for 2 minutes to form a first mixture; The cement, slag, remaining phosphogypsum, crushed stone, machine-made sand, admixtures and remaining water are placed in a forced mixer and stirred for 3 minutes to form a second mixture; The first mixed material and the second mixed material are mixed and stirred for 3 minutes to form a second mixed material; The formed third mixture is filled into a forming mold to form a self-compacting phosphogypsum road base material.
[0037] Among them, the preparation method of phosphogypsum is to crush the phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully turn and dry it to below the plastic limit, and distribute it in powder form, and the free moisture content should be less than 12%; then, the phosphogypsum is placed in a ball mill for ball milling to obtain a particle size of 5-50 μm.
[0038] The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.234; the water-to-cement ratio is 9; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.
[0039] Embodiment 2: A method for preparing a self-compacting phosphogypsum-based road base material comprises the following steps: Weigh the following base materials by mass percentage: phosphogypsum 45%, crushed stone 37.7%, machine-made sand 9%, cement 2%, slag powder 6.0%, admixture 0.3%; 85% of the total amount of phosphogypsum and 65% of the total amount of water are placed in a forced mixer and stirred for 2 minutes to form a first mixture; The cement, slag, remaining phosphogypsum, crushed stone, machine-made sand, admixtures and remaining water are placed in a forced mixer and stirred for 3 minutes to form a second mixture; The first mixed material and the second mixed material are mixed and stirred for 3 minutes to obtain a second mixed material; The formed third mixture is filled into a forming mold to form a self-compacting phosphogypsum road base material.
[0040] The preparation method of phosphogypsum comprises crushing the phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then, the phosphogypsum is placed in a ball mill for ball milling, and the particle size of the phosphogypsum is obtained to be 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.239, and the water-to-cement ratio is 7.4; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.
[0041] Embodiment 3: A method for preparing a self-compacting phosphogypsum-based road base material comprises the following steps: Weigh the following base materials by mass percentage: phosphogypsum 45%, crushed stone 37.5%, machine-made sand 9.0%, cement 2.2%, slag powder 5.9%, admixture 0.4%; 85% of the total amount of phosphogypsum and 65% of the total amount of water are placed in a forced mixer and stirred for 2 minutes to form a first mixture; The cement, slag, remaining phosphogypsum, crushed stone, machine-made sand, admixtures and remaining water are placed in a forced mixer and stirred for 3 minutes to form a second mixture; The first mixed material and the second mixed material are mixed and stirred for 3 minutes to form a second mixed material; The formed third mixture is filled into a forming mold to form a self-compacting phosphogypsum road base material.
[0042] The preparation method of phosphogypsum comprises crushing the phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then, the phosphogypsum is placed in a ball mill for ball milling, and the particle size of the phosphogypsum is obtained to be 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.240; the water-to-cement ratio is 6.7; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.
[0043] Embodiment 4: A method for preparing a self-compacting phosphogypsum-based road base material comprises the following steps: Weigh the following base materials by mass percentage: phosphogypsum 45%, crushed stone 37.5%, machine-made sand 9.2%, cement 2.14%, slag powder 5.84%, admixture 0.31%; 85% of the total amount of phosphogypsum and 65% of the total amount of water are placed in a forced mixer and stirred for 2 minutes to form a first mixture; The cement, slag, remaining phosphogypsum, crushed stone, machine-made sand, admixtures and remaining water are placed in a forced mixer and stirred for 3 minutes to form a second mixture; The first mixed material and the second mixed material were mixed and stirred for 3 minutes to form a second mixed material; The formed third mixture is filled into a forming mold to form a self-compacting phosphogypsum road base material.
[0044] The preparation method of phosphogypsum comprises crushing the phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then, the phosphogypsum is placed in a ball mill for ball milling, and the particle size of the phosphogypsum is obtained to be 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.245; the water-to-cement ratio is 6.97; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.
[0045] The self-compacting performance and mechanical property tests were performed on the phosphogypsum road base materials of Examples 1 to 4 above. The results are shown in Table 1.
[0046]
[0047] Example 5 A self-compacting phosphogypsum base road construction method comprises the following steps: S1 Construction preparation: Clean the construction site, use a sweeper to remove obstacles and debris from the pavement on the construction site, mark the contour and slope of the road according to the road design depth requirements, and then level and compact the road surface. The compaction degree should not be less than 94%, and the deflection of the roadbed top surface should not be greater than 248 (0.01mm). Sprinkle water to moisten the road surface before paving; S2 installation of construction formwork: the formwork system uses wooden formwork, and the back is reinforced with wooden square ribs. Before construction, the surveying personnel lay out the formwork installation edge line and use steel chisels to drive into the ground to fix it, ensuring that the formwork is firmly installed and must not loosen, run, or sink. The joints are tight and there is no leakage. The inside of the formwork is kept clean, and a line is drawn on the top of the formwork to mark the control line of the top surface of the base layer.
[0048] S3 base material mixing: (1) weighing 719 kg of phosphogypsum and 182.1 kg of water and placing them in a forced mixer and stirring for 2 minutes to form a first mixture; (2) placing 40.2 kg of cement, 109.8 kg of slag, 126.9 kg of phosphogypsum, 704.9 kg of crushed stone, 172.9 kg of machine-made sand, 5.8 kg of admixture and 98.1 kg of water in a forced mixer and stirring for 3 min to form a second mixture; (3) mixing the first mixture and the second mixture for 3 minutes to form a third mixture; (4) Filling the formed third mixture into a forming mold to form a self-compacting phosphogypsum road base material.
[0049] The preparation method of phosphogypsum comprises crushing the phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of 5-50 μm, and fully drying the phosphogypsum particles to below the plastic limit, dispersing the particles in powder form, and distributing the particles in a free moisture content of less than 12%. The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.245; the water-to-cement ratio is 6.97; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.
[0050] The water and modifier used are measured by coarse and fine metering, with two-stage batching. The initial large flow rate ensures efficiency, and the final small flow rate ensures accuracy. The valve is controlled to cut off and the flow is cut off quickly. S4 base paving: After the second mixture is evenly mixed, it is transported to the construction site. Before paving, the lower bearing layer is roughened, the inner side of the formwork is sprinkled with water to moisten it, and the concrete mixer truck is used for self-unloading paving, with manual assistance; a horizontal polyurethane expansion joint plate perpendicular to the center line of the road is left every 30 meters, and the expansion joint plate width is 20mm. After paving, the surface is leveled and roughened again; S5 Maintenance, cutting and grouting: After the base layer is paved, spray the surface with polymer curing agent twice for maintenance. The first spraying is done during initial setting, and the second spraying is done in the vertical direction after the curing agent basically forms a film. The maintenance time is not less than 7 days, and vehicles are prohibited from passing during the maintenance period. After final setting, cutting and grouting are carried out in time. A horizontal seam is cut perpendicular to the center line of the road every 10 meters using road cutting equipment. The seam width is 5-8mm and the depth is not less than 1 / 3 of the thickness of a single layer of base layer. After cutting, clean up the debris in the seam and grout it with asphalt paste. For the reserved horizontal polyurethane expansion joint plate, clean the top expansion joint to a depth of 2-3cm, and then grout it with asphalt paste.
[0051] During construction, the mixture is randomly inspected next to the mixer, and samples are kept as test pieces for standard curing test blocks to test strength; after curing, core samples are drilled and taken to test compressive strength, softening coefficient and water absorption rate, etc.
[0052] According to the above construction method, an engineering test was carried out. The test section was the motor vehicle lane of the Dianjun 1st Road (Juanqiaohe 2nd Road~Wulong 3rd Road) municipal engineering EPC project, namely K1+310~K1+490, a total of 170 meters.
[0053] The following test methods are used to conduct performance testing and economic and social benefit evaluation on the road base of the engineering test.
[0054] With reference to JGJ / T283-2012 "Technical Code for Application of Self-compacting Concrete" and its Appendix A.1, the self-compacting performance of the engineering verification test core samples was tested.
[0055] Referring to GBT / 50784-2013 "Technical Standard for On-site Testing of Concrete Structures", the mechanical properties of on-site core samples and standard-cured test blocks were tested.
[0056] According to the water absorption grade and test method of JGT / 266 "Foamed Concrete", the water absorption of on-site core samples and standard curing test blocks was tested.
[0057] With reference to the “Horizontal Oscillation Method for Toxicity Leaching of Solid Waste” (HJ557-2010), pollutants in self-compacting phosphogypsum road base materials were tested.
[0058] 1. Performance testing 1.1 Filling test The filling performance needs to test two indicators: slump expansion and expansion time. The test results are shown in Table 2.
[0059] Table 2 Slump expansion and expansion time of base material mixture
[0060] It can be seen from Table 2 that the slump expansion grade of the self-compacting phosphogypsum base material of the road base is SF1, and the expansion time (T500) grade is VS1, which meets the technical index requirements.
[0061] 1.2 Compressive strength The compressive strength after 7 days, 14 days and 28 days was measured by coring in the field test section and standard curing test blocks in the laboratory. The test results are shown in Table 3.
[0062] Table 3 Compressive strength test of on-site core samples and standard curing test blocks
[0063] It can be seen from Table 3 that through coring in the on-site test section and standard laboratory curing test blocks, the 28-day compressive strength can reach 5Mpa or above, meeting the technical index requirements.
[0064] 1.3 Softening coefficient The 14-day-old field core samples and standard-cured test blocks were divided into two groups. One group was immersed in water for 14 to 28 days, and its strength was tested. The strength was compared with that of the core samples and standard-cured test blocks at normal 28 days of age to obtain the 28-day water softening coefficient. The results are shown in Table 4.
[0065] Table 4 Water softening resistance test of on-site core samples and standard curing test blocks
[0066] It can be seen from Table 4 that after testing, the water softening coefficient is far more than 85%, and the core sample water-soaked strength is better than the strength growth under natural conditions, meeting the technical index requirements.
[0067] 1.4 Water absorption The water absorption rate of the 28-day-old field core samples and standard-cured test blocks was tested, and the data is shown in Table 5.
[0068] Table 5 Water absorption test of on-site core samples and standard curing test blocks
[0069] As shown in Table 5, the water absorption of the 28-day-old field core samples and standard-cured test blocks was tested, and the average water absorption was 5.57% and 5.58% respectively, both meeting the technical index requirements.
[0070] 1.5 XRD X-ray diffraction analysis was performed on samples of the self-compacting phosphogypsum base material mixture at 14d and 28d. The analysis results are shown in Figure 1 .
[0071] Comparing the XRD patterns of 14d and 28d samples of self-compacting phosphogypsum base materials, it can be seen that the content of ettringite is low and there is no obvious difference between the two ages, indicating that ettringite is not continuously generated with the increase of age, which is beneficial to the overall stability of the base structure.
[0072] 1.6 Environmental Assessment The adverse impact that self-compacting phosphogypsum base materials may have on the environment is mainly the precipitation of pollutants into the soil and surrounding environment after long-term immersion or scouring by rainwater. Therefore, the solid waste leaching toxicity leaching method is used to test it, and the test method adopts the horizontal oscillation method. The pollutant indicators of the core sample leachate of the self-compacting phosphogypsum base material at the age of 28 days are tested, and the results are shown in Table 6.
[0073] Table 6 Test results of pollutant precipitation in the leaching solution of core samples at 28 days of age
[0074] The test results show that after solidification and modification, the content of harmful substances in the material leachate meets the A standard of the first-level standard in the "Pollutant Discharge Standard for Urban Sewage Treatment Plants" (GB18918-2002): the basic requirements for the effluent from urban sewage treatment plants as landscape water and general recycled water, and meets the requirements of the discharge standards.
[0075] Based on the above test results, it can be seen that the self-compacting performance, mechanical properties and environmental impact of the road base paved with self-compacting phosphogypsum base material meet the technical standards.
[0076] 2. Economic and social benefits 2.1 Economic Benefits The economic comparison between self-compacting phosphogypsum base material and 5% cement stabilized crushed stone is shown in Table 6.
[0077] Table 7 Comparison of economic performance between self-compacting phosphogypsum base material and 5% cement stabilized crushed stone
[0078] It can be seen from the data in Table 7 that the overall cost of self-compacting phosphogypsum base material (45% phosphogypsum) used for road base is basically the same as that of conventional 5% cement-stabilized crushed stone base. If the large-scale comprehensive application of phosphogypsum in engineering in the later stage is taken into account, the cost of phosphogypsum raw materials and production costs will have a large downward space, and the promotion and application prospects are broad, with significant economic benefits.
[0079] 2.2 Social Benefits As solid waste, phosphogypsum replaces a large amount of aggregates in the road base. According to the stable base of 35,000 tons per highway of urban trunk roads, 45% phosphogypsum, about 15,800 tons of phosphogypsum slag is consumed per kilometer, which is equivalent to saving 15,800 tons of natural aggregates. It can better realize the resource utilization and large-scale efficient utilization of industrial waste slag, and produce good social benefits. At the same time, it greatly alleviates the difficulties of road engineering construction in areas with scarce mining stone resources, which is conducive to saving resources, energy saving and consumption reduction, and sustainable development of urban construction.
[0080] In summary, the present invention selects base materials in appropriate proportions and provides a self-compacting phosphogypsum base road construction process that does not require rolling. The process has the characteristics of reliable performance, simple process, and good economy, and can be widely used in bases of roads of various grades. In addition, the base road construction method provided by the present invention has a good effect on the control of base thickness and flatness, has a stable structure, is simple to operate, and is extremely convenient to install and disassemble, shortening the construction period. The materials can be reused, which is economical and practical. The construction method has significant beneficial effects and is suitable for application and promotion.
[0081] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A method for construction of a road with a self-compacting phosphogypsum base without rolling. It is characterized in that The following steps are involved: S1 Construction preparation: Clean the construction site, use a sweeper to remove obstacles and debris from the pavement on the construction site, mark the contour and slope of the road according to the road design depth requirements, and then level and compact the road surface. The compaction degree should not be less than 94%, and the deflection of the roadbed top surface should not be greater than 248 (0.01mm). Sprinkle water to moisten the road surface before paving; S2 base material preparation: phosphogypsum, cement, slag, aggregate and admixture, and water are used as raw materials for the phosphogypsum road base mixture, and various raw materials are centrifugally mixed according to a determined mass ratio to obtain a uniform and dense phosphogypsum base mixture; S3 base paving: transport the evenly mixed mixture to the construction site for paving. After paving, maintain it to form the road base.
2. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that Step S1 also includes installing the construction formwork: the formwork system uses a wooden formwork or a steel formwork, and the formwork should have sufficient strength, rigidity and overall stability. Before construction, the surveyor lays out the formwork installation edge line and uses a steel bar to drive it into the ground to fix it, ensuring that the formwork is firmly installed and must not be loose, run, or sink. The joints are tight and there is no leakage. The inside of the formwork is kept clean, and a line is drawn on the top of the formwork to mark the control line of the top surface of the base layer.
3. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that In step S2, the particle size of the phosphogypsum is 5-50 μm, the attached water (wet basis) is not more than 12%, and the content of calcium sulfate dihydrate (dry basis) is not less than 90%.
4. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that In step S2, the cement strength grade is ordinary Portland cement of 42.5, the fineness is expressed by the residue on a 45 μm square sieve, not less than 5%; the initial setting time is not less than 45 min, the final setting time is not more than 600 min; the stability is qualified by boiling method, the chemical requirement (mass fraction) is the loss on ignition is not more than 5%, SO 3 No more than 3.5%, MgO no more than 5%, chloride ion no more than 0.06%; The slag is S95 grade granulated blast furnace slag powder with a density of not less than 2.8g / cm 3 , specific surface area not less than 400m 2 / kg, 28-day activity index not less than 95%, fluidity ratio not less than 95%, initial setting time ratio not more than 200%, water content not more than 1%, SO 3 (mass fraction) is not more than 4%, the loss on ignition is not more than 1%, and the insoluble matter (mass fraction) is not more than 3%.
5. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that In step S2, the aggregate used is a mixture of crushed stone and sand. The crushed stone is graded crushed stone, which is fine crushed stone with a particle size of 5-10 mm and coarse crushed stone with a particle size of 10-20 mm, with a mass ratio of 3:7; the sand is machine-made fine sand with a particle size of less than 4.75 mm; and the sand-to-stone ratio is 0.2-0.
3.
6. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that In step S2, the mass ratio of the phosphogypsum, crushed stone, sand, cement, slag and admixture is 40-50:30-41:8-10:1-4:3-9:0.2-0.7; and the water-cement ratio is 4.5-7.
5.
7. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that In step S2, the mixture is mixed by uniformly mixing part of the phosphogypsum and an appropriate amount of water to form a first mixture; mixing the cementitious material, the remaining phosphogypsum, aggregate, admixture and the remaining water to form a second mixture; and mixing the first mixture and the second mixture to form a third mixture.
8. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 6, It is characterized in that The mixing is carried out by centrifugal mixing using a forced mixer.
9. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that Before paving, the underlying layer is roughened and the inside of the formwork is sprinkled with water to moisten it. During paving, a mixer truck is used for self-unloading pouring. A horizontal polyurethane expansion joint plate perpendicular to the center line of the road is left every 30 meters. The expansion joint plate is 20mm thick. In addition, manual assistance is used to control the elevation of the top surface of the base layer and the horizontal and vertical slopes. After paving, the surface is leveled and roughened to increase the roughness.
10. A method for constructing a road with a self-compacting phosphogypsum base without rolling according to claim 1, It is characterized in that Step S3 also includes maintenance, seam cutting and seam filling: after the base layer is paved, the surface is sprayed with a polymer curing agent twice for maintenance. The first spray is applied during initial setting, and the second spray is applied in a vertical direction after the curing agent has basically formed a film. The curing time is not less than 7 days, and vehicles are prohibited from passing during the curing period. After final setting, seam cutting and seam filling are carried out in a timely manner. A transverse contraction joint is cut perpendicular to the center line of the road every 10 meters using road cutting equipment. The seam width is 5-8mm and the depth is not less than 1 / 3 of the thickness of the single-layer base layer. After cutting, the debris in the seam is cleaned and the seam is filled with asphalt paste. The reserved transverse polyurethane expansion joint plate has its top expansion joint cleaned to a depth of 2-3cm, and then the seam is filled with asphalt paste.
